Ferroptosis plays a role in osteoarthritis - Ruba Altahla; Jamal Alshorman; Xu Tao (All Life)
In recent years, ferroptosis has been identified as a novel type of regulated cell death. As a cell death process, it differs from other processes like necrosis and apoptosis in the expression of morphology, biochemistry, and genetics. Ferroptosis provides a new view of programmed cell death. It is initiated by the oxidation of lipids, reactive oxygen species (ROS) formation and iron buildup within cells, leading to their demise. The identification of these biochemical events triggering ferroptosis has expanded understanding of controlled cellular suicide. A significant role of ferroptosis in osteoarthritis (OA) has been reported in recent studies. Both OA and ferroptosis exhibit anomalies in metabolism of iron, oxidation of lipids, and mitochondrial dysfunction. Nonetheless, our understanding of the specific genes involved in regulating ferroptosis in the context of OA is currently limited. Expanding our knowledge in this area could have profound implications for effectively managing and treating OA. This review offers an in-depth exploration of the molecular processes associated with ferroptosis. Furthermore, we discuss the roles of ferrioptosis in different aspects of osteoarthritis, encompassing the degradation of cartilage, synovitis, dysfunction of chondrocytes, and the manifestation of OA-related pain. We highlight the potential of targeting ferroptosis for OA treatment.